2023
DOI: 10.1186/s12915-023-01627-w
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNAs arising from synaptic host genes during human neuronal differentiation are modulated by SFPQ RNA-binding protein

Abstract: Background Circular RNA (circRNA) molecules, generated through non-canonical back-splicing of exon-exon junctions, have recently been implicated in diverse biological functions including transcriptional regulation and modulation of protein interactions. CircRNAs are emerging as a key component of the complex neural transcriptome implicated in brain development. However, the specific expression patterns and functions of circRNAs in human neuronal differentiation have not been explored. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 78 publications
0
1
0
Order By: Relevance
“…Another study found that circRNAs originating from exons in neuroepithelial stem cells (NES) in humans have a higher chance of having a genetic variation. Studies have shown that some circRNAs had increased in SFPQ ribonucleoprotein complexes and decreased expression due to SFPQ knockdown [ 129 ].…”
Section: Functions Of Circular Rnamentioning
confidence: 99%
“…Another study found that circRNAs originating from exons in neuroepithelial stem cells (NES) in humans have a higher chance of having a genetic variation. Studies have shown that some circRNAs had increased in SFPQ ribonucleoprotein complexes and decreased expression due to SFPQ knockdown [ 129 ].…”
Section: Functions Of Circular Rnamentioning
confidence: 99%